Band-gap engineering of zirconia by nitrogen doping in reactive HiPIMS: a step forward in developing innovative technologies for photocatalysts synthesis - Matei, Teodora; Tiron, Vasile; Jijie, Roxana; Bulai, Georgiana; Velicu, Ioana-Laura; Cristea, Daniel; Crăciun, Valentin (Frontiers in Chemistry, 2023)
In the global context of climate change and carbon neutrality, this work proposes a strategy to improve the light absorption of photocatalytic water-splitting materials into the visible spectrum by anion doping. In this framework, reactive high power impulse magnetron sputtering (HiPIMS) of a pure Zr target in Ar/N2/O2 gas mixture was used for the deposition of crystalline zirconium oxynitride (ZrO2-xNx) thin films with variable nitrogen doping concentration and energy band-gap. The nitrogen content into these films was controlled by the discharge pulsing frequency, which controls the target surface poisoning and peak discharge current. The role of the nitrogen doping on the optical, structural, and photocatalytic properties of ZrO2-xNx films was investigated. UV-Vis-NIR spectroscopy was employed to investigate the optical properties and to assess the energy band-gap. Surface chemical analysis was performed using X-ray photoelectron spectroscopy, while structural analysis was carried out by X-ray diffraction. The increase in the pulse repetition frequency This is a provisional file, not the final typeset article determined a build-up in the nitrogen content of the deposited ZrO2-xNx thin films from ~10 to ~25 at.%. This leads to a narrowing of the optical band-gap energy from 3.43 to 2.20 eV and endorses efficient absorption of visible light. Owing to its narrow bandgap, ZrO2-xNx thin films obtained by reactive HiPIMS can be used as visible light-driven photocatalyst. For the selected processing conditions (pulsing configuration and gas composition), it was found that reactive HiPIMS can suppress the hysteresis effect for a wide range of frequencies, leading to a stable deposition process with a smooth transition from compound to metal-sputtering mode.